Proses dan Strategi Penyeliaan - Syed Ahmad, Syed ldrus; Saaid, Othman (Penerbit Universiti Sains Malaysia, 1987)
The article attempts to look at supervision as part and parcel of the principal's job. Supervision In schools Is an Important aspect for Instructional Improvement. In spite of this, It Is being relegated to a secondary role in favour of the administrative tasks. In fact administrative tasks can be delegated to someone else but not supervisory tasks which require professional competencies on the part of the supervisor.